Characterization of Acid Deposition at Pasoh Forest Reserve and Sepang Fire-Peat Swamp - Tay, Ai Chen (2002)
Pasoh Forest Reserve is located away from industrialized or urbanized areas. As a remote area, therefore Pasoh Forest Reserve is important to provide baseline information on the level of soil acidification in Malaysia. Furthermore, studies on the natural fires soil such as Sepang fire-peat are rare in Malaysia. The investigation of natural fires soil is essential for comparison purposes to Pasoh Forest Reserve. Hence, the objective of the study was to determine the physico-chemical properties of soils at Pasoh Forest Reserve and Sepang fire-peat swamp for evaluating the extent of acid deposition. Six subplots with dimension of 1 m x 1 m x 1 m were selected at the Pasoh Forest Reserve, while, only one plot with dimension of 1 m x 1 m x 1m was dug at the Sepang fire-peat swamp. Soil samples were taken from every 10 cm layer until 1 m depth. For each soil sample, acidity (PH), moisture content, bulk density, electrical conductivity, available phosphate (P042), available sulphate (sol"), exchangeable acidity, exchangeable A1 and H, exchangeable base cations, effective cation exchangeable capacity (BeEC) and base saturation were determined. At top part of soil profile at Pasoh Forest Reserve, there was an A horizon, characterized by dark brown colour as a result of an accumulation of humified organic matter intimately mixed with mineral matter. Below the A horizon, there was an E horizon, which was lighter in colour and texture. Below the E horizon, there was an EB horizon, which was dominated by the properties of E master horizon but with some properties of B master horizon. The B horizon was granular, blocky, or prismatic structure. The Pasoh Forest Reserve soils are clayey and acidic. The natural soil fires at Sepang caused destruction of soil structure as well as its texture, thus no clear horizon could be observed and the soil was sandy. Throughout 1 m soil depth, Pasoh Forest Reserve and Sepang fire-peat soils showed variation of soil properties. The results indicated that Pasoh Forest Reserve soils were more acidic than Sepang fire-peat soils. By comparing to the Pasoh Forest Reserve soils, the Sepang fire-peat soils showed lower mean values in bulk density and exchangeable acidity, but higher mean values in electrical conductivity, pH, base saturation, available sulphate and available phosphate. Sepang fire-peat soils were also showed relatively high values in exchangeable Mg and Ca, but low values in exchangeable K and Na. Furthermore, mean base saturation values of Sepang fire-peat soils and Pasoh Forest Reserve soils were 97.87 ± 2.42% and 78.77 ± 3.78%, respectively. The base saturation ofPasoh Forest Reserve soil was strongly correlated with the exchangeable Ca, whereas the base saturation of Sepang fire-peat soil was strongly correlated with exchangeable acidity. The significant differences between Pasoh Forest Reserve and Sepang firepeat soils were attributable to changes of soil composition after soil fires in Sepang causing mineral transformation. However, the physico-chemical properties of Pasoh Forest Reserve soils were similar to the previous findings by the Allbrook (1973) and Yoda (1978). Thus, the Pasoh Forest Reserve soils were presumably not unaffected by acid deposition. Additionally, there was no appreciable soil acidification occurred in the Pasoh Forest Reserve since 1973 (29 years).